Cellulose supported promising magnetic sorbents for magnetic solid-phase extraction: A review. (1st February 2021) - Mhd. Haniffa, Mhd. Abd. Cader; Ching, Yern Chee; Illias, Hazlee Azil; Munawar, Khadija; Ibrahim, Shaliza; Nguyen, Dai Hai; Chuah, Cheng Hock
Highlights: Preparation of cellulose supported promising magnetic sorbents (CMS) is summarized. Physical performance of the magnetic nanoparticles is discussed. Chemical attraction of magnetic nanoparticles towards cellulose substrates is summarized. CMS in the field of heavy metal, organic pollutants, and protein adoption is discussed. Advantages, challenges, and future of CMS in magnetic solid-phase extraction are provided. Abstract: Cellulose with ample hydroxyl groups is considered as a promising supportive biopolymer for fabricating cellulose supported promising magnetic sorbents (CMS) for magnetic solid-phase extraction (MSPE). The easy recovery via external magnetic field, and recyclability of CMS, associated with different types and surface modifications of cellulose has made them a promising sorbent in the field of solid-phase extraction. CMS based sorbent can offer improved adsorption and absorption capabilities due to its high specific surface area, porous structure, and magnetic attraction feature. This review mainly focuses on the fabrication strategies of CMS using magnetic nanoparticles (MNPs) and various forms of cellulose as a heterogeneous and homogeneous solution either in alkaline mediated urea or Ionic liquids (ILs). Moreover, CMS will be elaborated based on their structures, synthesis, physical performance, and chemical attraction of MNPs and their MSPE in details. The advantages, challenges, and prospects of CMS in future applications are also presented.